(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The cellphone is at the epicenter of a major technological revolution in today's digital culture, one that is having far reaching effects across many fields. Students’ utilization of cellphone has been a topic of study in institutions of higher learning. Previous research on the topic of students' utilization of cellphone and academic performance has largely concentrated on quantifying the effect that students' cellphone use has on their academic performance. The goal of this research is to determine whether or not gender differences and prior exposure to a certain social interactions and learning environment have a role in the adoption of cellphones for educational purposes. A standardized self-report questionnaire was used to gather data from 347 first year students and 254 final year students of the Federal Polytechnic, Ado Ekiti, Nigeria (FPA). Our research is motivated by a desire to answer the following questions about how the utilization of cellphone by students affects their academic performance. Firstly, to investigate the pattern of the utilization of cellphone amongst the students’ genders for academic purposes. Secondly, to explore how much of an impact the learning environment has on students' cellphone use in order to improve their academic performance outcome and thirdly how much of an impact the utilization of cellphone has on students' overall academic performance. In conclusion, we believe that a student's decision to use a smartphone for education tasks, partly depends on the student's level of comfort in and understanding of the numerous settings that comprise his or her learning environment. To better understand how students perceive cellphone use, and how that perception influences their academic performance results, we recommend using a range of data gathering methodologies for future study on the association between cellphone utilization and academic performance of students.